2014
DOI: 10.1007/s00294-014-0421-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes in Penicillium echinulatum to enable gene expression study using real-time quantitative RT-PCR

Abstract: Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) is a methodology that facilitates the quantification of mRNA expression in a given sample. Analysis of relative gene expression by qRT-PCR requires normalization of the data using a reference gene that is expressed at a similar level in all evaluated conditions. Determining an internal control gene is essential for gene expression studies. Gene expression studies in filamentous fungi frequently use the β-actin gene (actb), β-tubulin, and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Quantification of miRNAs and mRNA using quantitative real-time PCR Quantification of miR-221 and miR-222 in the G418-selected clones was performed by using SYBR Premix Ex Taq II (Perfect Real Time) assays (Applied TaKaRa Biosystems), followed by detection with the CFX96TM PCR detection system (Bio-Rad Laboratories, Hercules, CA, USA) according to the manufacturer's instructions (Technote 5859). The real-time quantitative PCR reaction conditions were as follows: denaturation at 95 1C for 5 min, followed by 40 cycles of denaturation at 95 1C for 10 s and annealing and extension at 60 1C for 30 s. 36 The U6 small nuclear RNA (Guanzhou Ribobio, Guanzhou, China) was used to normalize the relative abundance of miR-221 and miR-222. Data shown represent three independent experiments performed in triplicate.…”
Section: Rna Extractionmentioning
confidence: 99%
“…Quantification of miRNAs and mRNA using quantitative real-time PCR Quantification of miR-221 and miR-222 in the G418-selected clones was performed by using SYBR Premix Ex Taq II (Perfect Real Time) assays (Applied TaKaRa Biosystems), followed by detection with the CFX96TM PCR detection system (Bio-Rad Laboratories, Hercules, CA, USA) according to the manufacturer's instructions (Technote 5859). The real-time quantitative PCR reaction conditions were as follows: denaturation at 95 1C for 5 min, followed by 40 cycles of denaturation at 95 1C for 10 s and annealing and extension at 60 1C for 30 s. 36 The U6 small nuclear RNA (Guanzhou Ribobio, Guanzhou, China) was used to normalize the relative abundance of miR-221 and miR-222. Data shown represent three independent experiments performed in triplicate.…”
Section: Rna Extractionmentioning
confidence: 99%
“…A large number of research papers have been published on reference genes under different stresses or from different organs in plants (Warzybok and Migocka 2013; Lin et al 2014), and similar works in filamentous fungi are gradually being conducted (Zampieri et al 2014; Zhou et al 2011). It is striking that most of the applied reference genes for fungi were directly copied from the existing results in plants or animals, such as actin , tubulin and 18S rRNA (Fang and Bidochka 2006; Yan and Liou 2006).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ to the findings of Anita et al 10 . ACT1, TUB1, and SDHA are also commonly utilized reference genes in stability analysis and target gene expression studies 10,17,[34][35][36]38 . A study by Li et al clearly demonstrated the unsuitability of ACT1, TUB1, and SDHA as reference genes for inducible expression analysis in C. glabrata cells treated with fluconazole 17 .…”
Section: Discussionmentioning
confidence: 99%